Bezpečnost modelu pneumatického lisu - Nešpor, Tomáš (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2012)
Práce se zabývá funkční bezpečností strojních zařízení, konkrétně zabezpečením modelu pneumatického lisu. V dokumentu je stručné seznámení s normami, které určují bezpečnostní standardy při návrhu bezpečného strojního zařízení. V další části je uvedena analýza rizik psaná formou technické zprávy. V analýze rizik jsou identifikována možná rizika, která by se mohla vyskytnout při práci se strojem. Dále jsou uvedena bezpečnostní opatření vyplývající ze zjištěných rizik, seznam prvků, které byly použity pro bezpečnostní řízení pneumatického lisu a evaluace rizik dle normy ČSN EN ISO 13849-1. V části Programování zařízení je návod na konfiguraci zařízení a popis řídicího programu. Popis vizualizace v programu FactoryTalk je v poslední části práce.

This thesis is concerning functional safety of machinery, concretely safeguard of model of pneumatic press. In the document is briefly introduced norm, which determines safety standards during designing of safe machine. In the next part is mentioned risk assessment written as technical report. In risk assessment are identified possible risks that could appear during working on machine. Furthermore there are listed safety precautions ensuing from assessed risks, list of elements which has been used to safety control of pneumatic press and evaluation of risks according to EN ISO 13849-1 norm. In the part Programming of the device (Programování zařízení) is configuration manual of the device and description of control programme. The description of visualization in FactoryTalk programme is at the end of this thesis.
Safety of pneumatic press model
Keywords: Funkční bezpečnost; analýza rizik; bezpečnostní prvky; bezpečností normy; model lisu; DeviceNet; RSNetworx; SISTEMA; FactoryTalk; Functional safety; risk assessment; safety components; safety standards; model of pneumatic press; DeviceNet; RSNetworx; SISTEMA; FactoryTalk